Spectroscopic characterization of poly(ortho -aminophenol) film electrodes: A review article - Tucceri, Ismael Ricardo (2013)
This paper refers to spectroscopic studies carried out to identify the products of o-aminophenol electro-oxidation and elucidate the structure of electrochemically synthesized poly(o-aminophenol) (POAP) films. Spectroscopic studies of the redox conversion of POAP are also reviewed.